1964
DOI: 10.1093/bja/36.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Oedema and Cyanosis of the Hand Following Injections Into a Vein on the Dorsum of the Hand

Abstract: A case is described in which cyanosis and oedema of the hand and wrist followed injections into a vein on the dorsum of the hand. This was treated with intra-arterial procaine and block of the stellate ganglion. Possible causes for this reaction are venous spasm followed by thrombosis, leakage, reflex arterial and venous spasm and histamine release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…According to Walker et al the increased capillary permeability may be aggravated by the biotoxins that accumulate at the site of the occlusion because of acute limb ischemia. 5 Research by Ellertson et al also supports the view that the venospasm and associated thrombosis lead to outflow obstruction, followed by cyanosis, transudation, edema, and finally arterial stasis which lead to ischemic necrosis 6 In a case reported by Webster et al 7 similar dramatic cyanosis and swelling of the hand as in our case was observed after an injections given in the veins on the dorsum of the hand. The reporter suggested the possibility ofa venous spasm, followed by venous thrombosis as the cause of the vascular changes.…”
Section: Discussionsupporting
confidence: 78%
“…According to Walker et al the increased capillary permeability may be aggravated by the biotoxins that accumulate at the site of the occlusion because of acute limb ischemia. 5 Research by Ellertson et al also supports the view that the venospasm and associated thrombosis lead to outflow obstruction, followed by cyanosis, transudation, edema, and finally arterial stasis which lead to ischemic necrosis 6 In a case reported by Webster et al 7 similar dramatic cyanosis and swelling of the hand as in our case was observed after an injections given in the veins on the dorsum of the hand. The reporter suggested the possibility ofa venous spasm, followed by venous thrombosis as the cause of the vascular changes.…”
Section: Discussionsupporting
confidence: 78%